Evaluation of CD10 Expression and Its Relationship with Gleason Score in Prostatic Adenocarcinoma - A Ghasemi (Babol University of Medical Sciences, 2021)
BACKGROUND AND OBJECTIVE: CD10 is a zinc-dependent metalloproteinase that is associated with factors influencing the prognosis of some cancers. Prostatic adenocarcinoma is one of the most common cancers in men and Gleason grading is an important factor in its prognosis. The present study was conducted to investigate the relationship between immunohistochemical expression of CD10 and Gleason score as an indicator of prognosis in prostatic adenocarcinoma. METHODS: In this cross-sectional study, 60 paraffin blocks of prostatic adenocarcinoma samples from patients referred to Shahid Mostafa Khomeini Hospital in Tehran from 2013 to 2017 were immunohistochemically stained according to CD10 marker. Information about Gleason score was obtained by observing stained slides by hematoxylin and eosin staining method. The percentage of CD10 positive tumor cells was determined by primary and secondary Gleason score and the relationship between CD10 expression and Gleason score was evaluated. FINDINGS: The mean age of patients was 71±8.79 years. The percentage of CD10 expression varied from 5% to 62% in different samples. The mean percentages of CD10 expression in tumor cells in primary Gleason scores 2 to 5 were 10.75%, 16.16%, 35.20% and 44%, respectively and in secondary Gleason scores 2 to 5 were 10.38%, 17.08%, 38.19% and 53.5%, respectively (p<0.001). CONCLUSION: According to the results of this study, the immunohistochemical marker CD10 has a variable expression in prostatic adenocarcinoma and its increased expression is associated with an increase in the microscopic Gleason score of tumor as a factor influencing the prognosis.